2021
DOI: 10.33549/physiolres.934778
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Muscle Performance Deterioration in Sarcopenia Correlates With Circulating Muscle Tissue-Specific miRNAs

Abstract: Sarcopenia is defined as an age-associated loss of skeletal muscle function and muscle mass and is common in older adults. Sarcopenia as a disease is currently of interest not only to orthopedists and surgeons but also to internists, endocrinologists, rheumatologists, cardiologists, diabetologists, gynaecologists, geriatricians and paediatricians. In cooperation with the 5th Internal Medicine Clinic, we, as a unit of clinical research, aimed to describe a sarcopenic specific miRNA expression profile for diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Chen et al [ 32 ], examining miR-1-3p, -21-5p, -23a-3p, -24-3p, -100-5p, -125b-5p, -133a-3p, and -206 in the serum of 65 patients, did not find a specific alteration of circulating miRs. In contrast to the study of Chen et al [ 32 ], other studies found that patients with low muscle performance (sarcopenic) showed increased expression of miR-1, miR-29a, and miR-29b, but also a decreased expression of miR-486, miR-146a, miR-206, miR-133a, miR-133b, miR-208b, and miR-499 [ 82 , 83 ]. Alteration in circulating miRs was also demonstrated by He et al: examining plasma from sarcopenic and non-sarcopenic patients showed that miR-155, miR-208b, miR-222, miR-210, miR-328, and miR-499 were significantly down-regulated in sarcopenic compared to non-sarcopenic patients [ 80 ].…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Chen et al [ 32 ], examining miR-1-3p, -21-5p, -23a-3p, -24-3p, -100-5p, -125b-5p, -133a-3p, and -206 in the serum of 65 patients, did not find a specific alteration of circulating miRs. In contrast to the study of Chen et al [ 32 ], other studies found that patients with low muscle performance (sarcopenic) showed increased expression of miR-1, miR-29a, and miR-29b, but also a decreased expression of miR-486, miR-146a, miR-206, miR-133a, miR-133b, miR-208b, and miR-499 [ 82 , 83 ]. Alteration in circulating miRs was also demonstrated by He et al: examining plasma from sarcopenic and non-sarcopenic patients showed that miR-155, miR-208b, miR-222, miR-210, miR-328, and miR-499 were significantly down-regulated in sarcopenic compared to non-sarcopenic patients [ 80 ].…”
Section: Resultsmentioning
confidence: 77%
“…All the studies on sarcopenia [ 32 , 81 , 82 , 83 ] satisfied all the items in the QUADAS2, which suggests that the overall quality of the included studies was high.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In another study, Valášková et al analyzed the expression of myomiRs in blood samples of patients with low muscle performance [ 132 ]. Among many, they observed a decrease in the expression of miR-208b and miR-499.…”
Section: Sarcopenia–exclusive Mirnasmentioning
confidence: 99%